Toward Improved Accuracy Standards for Hydrographic Surveying - Alper, Stanley; Bossler, John D. (The International Hydrographic Review, 2015)
During a routine review of hydrographic procedures, we became aware that the hydrographic survey standards published by the IHO [1] and our own agency [2] are not stated in terms of statistical parameters as is the case in most sciences, e.g. in geodesy. Digging a little deeper, though not exhaustively, we found that some of the published standards are either ambiguous, unrealistic, or not definitive. This is true for both depth and horizontal positioning standards.